Shifting Power? Assessing the Impact of Transparency and Accountabilit y Initiatives - McGee, Rosie; Gaventa, John (IDS, 2011)
This paper arises from a review of the impact and effectiveness of tra nsparency and accountability initiatives which gathered and analysed e xisting evidence, discussed how it could be improved, and ev...